Method for testing tensile strength of rock sample

By using spherical samples and cohesive numerical models combined with acoustic emission technology, the problem of inability to effectively characterize the tensile strength of three-dimensional rocks in the prior art is solved, and a more accurate three-dimensional tensile strength test is achieved.

CN119437888APending Publication Date: 2025-02-14SHIJIAZHUANG TIEDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411625414.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing tensile strength testing methods, especially Brazilian splitting method, cannot effectively characterize the true tensile strength of three-dimensional rocks, because its stress concentration area is small, and the crack will definitely expand along the maximum main stress surface, which is pre-set. Pull the section.

Method used

Tensile strength tests were tested using spherical samples, combined with cohesive numerical model and acoustic emission technology, and through numerical simulation and experimental data analysis, a numerical model of rock samples was established, axial compression was performed, stress distribution data and potential rupture surfaces were obtained. , judge the three-dimensional tensile strength of the rock.

Benefits of technology

Through spherical sample testing, the three-dimensional tensile strength of the rock can be more accurately reflected, providing new research ideas, and better reflecting the tensile and breaking characteristics of the rock.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119437888A_ABST
    Figure CN119437888A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of rock mechanical tests, and discloses a rock sample tensile strength testing method which comprises the following steps: acquiring a spherical rock sample and a disc rock sample, performing mechanical tests on each rock sample, recording data, calculating tensile strength values, and preliminarily judging the three-dimensional tensile strength of the rock samples according to the tensile strength values. And in combination with experimental data and the tensile strength value, establishing a numerical model by utilizing numerical software, obtaining stress distribution and a potential fracture surface through axial compression, and further judging the three-dimensional tensile strength. And simulating a fracture process through a cohesion numerical model, capturing an acoustic emission event by adopting an acoustic emission technology, and evaluating the three-dimensional tensile strength again. And comparing the results of the steps to obtain a conclusion that the three-dimensional tensile strength of the spherical sample is smaller than that of the disc sample. According to the technical scheme provided by the invention, the fracture process and acoustic emission distribution characteristics of the spherical sample can be deeply researched, and the spherical sample can more easily reflect the three-dimensional tensile fracture characteristics of the rock in a three-dimensional state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rock mechanics testing, and in particular relates to a method for testing the tensile strength of a rock sample. Background Art

[0002] The tensile strength of rock is an important parameter in rock mechanics, which directly determines the stability of engineering rock mass. Studies have shown that most of the damage in engineering rock mass is caused by tensile failure. Therefore, accurately obtaining the value of rock tensile strength is of great significance to engineering construction. At present, the commonly used tensile strength test methods are direct tensile method and indirect tensile method. There are many problems in testing the tensile strength of rock by direct tensile method. Although scholars at home and abroad have improved and optimized the direct tensile test fixture, which greatly reduced the eccentric tension problem, the direct tensile method is complicated to operate and needs to overcome many problems such as the connection between the sample and the testing machine. Therefore, the indirect tensile method for testing the tensile strength of rock came into being.

[0003] The Brazilian splitting method is the most commonly used in the indirect tensile test of rock tensile strength. The International Society of Rock Mechanics (ISRM) recommends the Brazilian splitting method as an indirect method for testing tensile strength. Since then, other countries have also included this method in relevant technical specifications, and scholars have conducted a lot of research on this. Although the Brazilian splitting method is simple and easy to implement, it also has a defect. During the Brazilian disc test, the stress concentration area is small, and the crack will inevitably extend along the maximum principal stress surface, which is equivalent to pre-setting the tensile fracture surface. The test result can be considered as the tensile strength value of the tensile fracture surface, which cannot represent the true tensile strength of three-dimensional rocks. Summary of the invention

[0004] The purpose of the present invention is to provide a method for testing the tensile strength of a rock sample to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides a method for testing the tensile strength of a rock sample, comprising:

[0006] Step 1: obtaining rock samples, wherein the rock samples include spherical samples and disc samples;

[0007] Step 2: Perform mechanical tests on each of the rock samples, record experimental data and calculate the tensile strength value of each of the rock samples, and determine the three-dimensional tensile strength of each of the rock samples based on the tensile strength value of each of the rock samples;

[0008] Step 3: Based on the experimental data and the tensile strength value, a numerical model of each of the rock samples is established in combination with numerical software, and the established numerical model is axially compressed to obtain stress distribution data and potential fracture surfaces of each of the rock samples, and the three-dimensional tensile strength of each of the rock samples is determined based on the stress distribution data and potential fracture surfaces corresponding to each of the rock samples;

[0009] Step 4: simulating the fracture process of each of the rock samples according to the cohesive force numerical model, and obtaining the acoustic emission events during the fracture process using the acoustic emission technology; judging the three-dimensional tensile strength of each of the rock samples based on the acoustic emission events corresponding to each of the rock samples;

[0010] Step 5: Based on the judgment results of steps 2 to 4, the three-dimensional tensile strength of each rock sample is compared to obtain a comparison result, wherein the comparison result is that the three-dimensional tensile strength of the spherical sample is less than the three-dimensional tensile strength of the disc sample.

[0011] Optionally, before performing mechanical tests on each of the rock samples, the method further includes:

[0012] Vaseline is applied to both ends of each rock sample to obtain each pretreated rock sample, and mechanical tests are performed based on each pretreated rock sample.

[0013] Optionally, the mechanical test on each of the rock samples specifically includes:

[0014] Mechanical tests are performed on each of the rock samples using a rock mechanics testing machine combined with a preset loading rate.

[0015] Optionally, the recording of experimental data and calculating the tensile strength value of each rock sample specifically includes:

[0016] During the mechanical test of each of the rock samples, a displacement-load curve is recorded;

[0017] The peak load is extracted from the displacement-load curve and the tensile strength value is calculated.

[0018] Optionally, judging the three-dimensional tensile strength of each of the rock samples based on the tensile strength value of each of the rock samples specifically includes:

[0019] The standard deviation corresponding to the tensile strength value of each of the rock samples is calculated. When the standard deviation is less than a preset first threshold value, the rock sample has low three-dimensional tensile strength.

[0020] Optionally, the process of acquiring the stress distribution data and potential fracture surface of each rock sample specifically includes:

[0021] Establishing a geometric model of the rock sample in ABAQUS based on the experimental data and the tensile strength value;

[0022] The boundary conditions and loading methods during the axial compression process are simulated in the constructed geometric model, and finite element analysis is performed to obtain the horizontal stress distribution data of the rock sample during the axial compression process, and the potential fracture surface of the rock sample is determined based on the horizontal stress distribution data.

[0023] Optionally, judging the three-dimensional tensile strength of each rock sample based on the stress distribution data and potential fracture surface corresponding to each rock sample specifically includes:

[0024] When the stress distribution data corresponding to the rock sample is distributed in a ring shape on a three-dimensional surface, the corresponding rock sample has a low three-dimensional tensile strength;

[0025] When the potential fracture surfaces corresponding to the rock sample are randomly distributed, the corresponding rock sample has low three-dimensional tensile strength; when the potential fracture surfaces corresponding to the rock sample are predictedly distributed, the corresponding rock sample has high three-dimensional tensile strength.

[0026] Optionally, simulating the fracture process of the spherical rock sample according to the cohesive force numerical model specifically includes:

[0027] A linear elastic constitutive model is used to describe the stress-strain relationship of the cohesive unit before damage, and the crack extension criterion is set. A numerical model of mineral heterogeneity is established based on the results of mineral composition analysis. A zero-thickness cohesive unit is embedded in the middle of the solid unit, and fracture parameters are set to complete the cohesive force numerical model of the rock sample.

[0028] Based on the acoustic emission numerical simulation method, the time-load curve and acoustic emission event distribution diagram in the cohesive force numerical model are obtained.

[0029] Optionally, judging the three-dimensional tensile strength of each rock sample based on the acoustic emission events corresponding to each rock sample specifically includes:

[0030] When the acoustic emission events corresponding to the rock sample are discretely distributed in three-dimensional space, the corresponding rock sample has low three-dimensional tensile strength.

[0031] The technical effects of the present invention are:

[0032] The present invention uses spherical specimens to carry out tensile strength test and conducts comparative study with the traditional Brazilian splitting method. Combined with the cohesive force model, the numerical simulation analysis of the tensile strength of the two specimens is carried out. Through the numerical simulation method of acoustic emission developed by programming, the fracture process and acoustic emission distribution characteristics of spherical specimens and Brazilian disc specimens are deeply studied, which is easier to reflect the tensile fracture characteristics of rocks in a three-dimensional state, and provides a new research idea for the tensile strength test method. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0035] Figure 1 A physical picture of a sample in an embodiment of the present invention;

[0036] Figure 2 is a schematic diagram of a displacement-load curve in an embodiment of the present invention;

[0037] Figure 3 Schematic diagram of the tensile strength of two samples in the embodiment of the present invention;

[0038] Figure 4 Schematic diagram of the rupture morphology in an embodiment of the present invention;

[0039] Figure 5 The stress and potential fracture surface of the Brazilian disk in the embodiment of the present invention;

[0040] Figure 6 The spherical stress and potential fracture surface in the embodiment of the present invention;

[0041] Figure 7 is a schematic diagram of a numerical model in an embodiment of the present invention;

[0042] Figure 8 The load curve and the number of acoustic emission events in the embodiment of the present invention are (a) spherical sample (b) disc sample;

[0043] Fig. 9 is a diagram of the spatiotemporal evolution of acoustic emission in an embodiment of the present invention;

[0044] Fig.10 is the number of acoustic emission events in the embodiment of the present invention;

[0045] Fig.11 is a stress cloud diagram of a spherical specimen in an embodiment of the present invention;

[0046] Fig.12 is a stress diagram in the diameter direction of the loading point of the spherical sample in an embodiment of the present invention;

[0047] Fig.13 It is a test flow chart in an embodiment of the present invention. DETAILED DESCRIPTION

[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0049] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art generally understood by the present invention. Although the present invention describes only preferred methods, any method similar or equivalent to that described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0052] The words “include,” “including,” “have,” “contain,” etc. used in this article are open-ended terms, meaning including but not limited to.

[0053] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0054] Embodiment 1

[0055] like Figure 1 - Fig.13 As shown, this embodiment provides a rock sample tensile strength testing method, comprising:

[0056] Step 1: obtaining rock samples, wherein the rock samples include spherical samples and disc samples;

[0057] Step 2: Perform mechanical tests on each of the rock samples, record experimental data and calculate the tensile strength value of each of the rock samples, and determine the three-dimensional tensile strength of each of the rock samples based on the tensile strength value of each of the rock samples;

[0058] Step 3: Based on the experimental data and the tensile strength value, a numerical model of each of the rock samples is established in combination with numerical software, and the established numerical model is axially compressed to obtain stress distribution data and potential fracture surfaces of each of the rock samples, and the three-dimensional tensile strength of each of the rock samples is determined based on the stress distribution data and potential fracture surfaces corresponding to each of the rock samples;

[0059] Step 4: simulating the fracture process of each of the rock samples according to the cohesive force numerical model, and obtaining the acoustic emission events during the fracture process using the acoustic emission technology; judging the three-dimensional tensile strength of each of the rock samples based on the acoustic emission events corresponding to each of the rock samples;

[0060] Step 5: Based on the judgment results of steps 2 to 4, the three-dimensional tensile strength of each rock sample is compared to obtain a comparison result, wherein the comparison result is that the three-dimensional tensile strength of the spherical sample is less than the three-dimensional tensile strength of the disc sample.

[0061] In view of the problems existing in the current indirect method for testing the tensile strength of rocks, this embodiment carried out an exploratory test on the tensile strength testing of spherical specimens, and combined with the numerical analysis of the cohesive force model, discussed the similarities and differences between the tensile strength testing of spherical specimens and traditional Brazilian disc specimens, and proposed the unique advantages of spherical specimens in obtaining the tensile strength of rocks. The research results provide new ideas for the tensile strength testing method.

[0062] Accurately obtaining the tensile strength value of rock is of great significance for guiding the stable construction of rock engineering. In this embodiment, a tensile strength test was carried out using a spherical specimen, and a comparative study was conducted with the traditional Brazilian splitting method. Combined with the cohesive force model, a numerical simulation analysis of the tensile strength of the two specimens was carried out. Through the numerical simulation method of acoustic emission developed by programming, the fracture process and acoustic emission distribution characteristics of the spherical specimen and the Brazilian disc specimen were deeply studied, and the similarities and differences between the test results of the two specimens were compared and analyzed. During axial compression, the stress distribution of the Brazilian disc specimen is more concentrated, the tensile acoustic emission events are concentrated in the middle of the specimen, the potential fracture surface range is limited, and the tensile strength value obtained is more inclined to the strength parameter of a certain section. The stress concentration area of ​​the spherical specimen is more widely distributed, and the potential fracture surface position will not be pre-defined, which increases the randomness of rock fracture. The low-energy acoustic emission events are discretely distributed in three-dimensional space, and there is a weakest fracture surface with high-energy acoustic emission characteristics, showing a more obvious three-dimensional effect. The standard deviation of the results obtained from the spherical specimen is small, the tensile shear ratio is large, and the tensile strength value is about 0.5 times that of the Brazilian disc specimen. The tensile strength value obtained is easier to reflect the tensile fracture characteristics of the rock in a three-dimensional state. The test results of this embodiment provide new research ideas for the tensile strength test method.

[0063] The specific implementation process of this embodiment includes:

[0064] This experiment uses dense sandstone samples from the Sichuan Basin, which are polished into spherical samples with a diameter of 50mm by a stone processing factory to ensure that the diameter size error on the entire spherical surface is no more than 0.5mm. At the same time, in order to conduct experimental comparisons with the Brazilian splitting method, a 50mm×25mm (diameter×thickness) Brazilian disc sample was processed on the same piece of sandstone raw stone. According to the requirements of the rock mechanics experimental specifications, the diameter of the disc sample throughout the thickness and the non-parallelism at both ends are guaranteed to be within the error range. Before the start of the test, the sample size is measured, and the loading points at both ends of the spherical sample are marked to determine the longitudinal distance between the two loading points. To ensure the reliability of the results, five groups of spherical samples and Brazilian disc samples are processed respectively. The spherical samples are numbered Q1~Q5, and the disc samples are numbered S1~S5( Figure 1 ), the sample dimensions are shown in Table 1.

[0065] Table 1 Sample size

[0066]

[0067] After the sample preparation was completed, the American-made MTS-CMT5105 rock mechanics testing machine of the Institute of Geology and Geophysics, Chinese Academy of Sciences was used as the experimental loading system. The maximum load of the testing machine is 100kN. During the experiment, vaseline was applied to both ends of the sample to reduce the friction between the sample and the loading plate, and the loading rate was controlled at 0.06mm / min.

[0068] Mechanical characteristics: According to the test mechanical data obtained by the rock mechanics testing machine, the displacement-load curves of the spherical specimen and the Brazilian disc specimen can be obtained ( Figure 2 ). According to the displacement-load curves of the spherical specimens and Brazilian disc specimens, it can be found that the displacement-load curve stages of the two specimens correspond to the stages of the total stress-strain curves, and both have relatively obvious initial compaction stages and linear elastic stages, while the plastic stages of the two specimens are not very obvious. After the load reaches the peak value, the specimen breaks and the load drops sharply, showing obvious brittle characteristics. Compared with the Brazilian disc, the initial compaction stage of the spherical specimen is shorter and the compaction characteristics are weaker. In addition, the displacement-load curve of the spherical specimen is more discrete. This is due to the three-dimensional characteristics of the spherical specimen. The micro-defects inside it are richer than those of the disc specimen, and the distribution is more complex. The differences between each specimen are more obvious, which leads to differences in the rate of change of load with displacement between specimens.

[0069] Experimental result data: According to the displacement-load curve obtained, the peak load of each specimen can be obtained, and thus the tensile strength value of the specimen can be obtained. The tensile strength formula of spherical specimens has been given by Hiramatsu:

[0070]

[0071] Among them, σ t is the tensile strength value, P is the peak load, and r is the radius of the spherical specimen.

[0072] For Brazilian disc specimens, the tensile strength value can be obtained by the following formula:

[0073]

[0074] Among them, σ t is the tensile strength value, P is the peak load, D is the diameter of the disc specimen, and t is the thickness of the disc specimen.

[0075] The peak load of each sample was extracted, and the tensile strength values ​​of the two samples were obtained as shown in Table 2 and Figure 3 As shown:

[0076] Table 2 Test results

[0077]

[0078] According to the calculation results in Table 2, it is found that the tensile strength of the spherical specimen is much smaller than that of the Brazilian disc specimen, with an average tensile strength of 3.3MPa, while the average tensile strength of the Brazilian disc specimen is 6.24MPa, which is about twice that of the spherical specimen. The reason is that the three-dimensional characteristics of the spherical specimen are more obvious, which increases the randomness of the crack rupture direction. The crack is bound to rupture along the weakest section of the three-dimensional specimen, while the Brazilian disc specimen is more inclined to the tensile strength value of a certain section. Therefore, the tensile strength value obtained by the spherical specimen is smaller than that of the Brazilian disc.

[0079] In addition, the tensile strength values ​​obtained from both types of specimens are discrete, and the standard deviation of the spherical specimen is 0.24, which is smaller than that of the Brazilian disc specimen. The obtained tensile strength values ​​are less discrete and can better reflect the true tensile strength value of three-dimensional rock.

[0080] Fracture morphology: In order to further analyze the fracture characteristics of the two samples, the rock samples after fracture were obtained, such as Figure 4 shown.

[0081] according to Figure 4 The final fracture morphology shows that the cracks of the Brazilian disc specimen are mainly distributed in the middle of the disc specimen, in a strip-like distribution, and there are tiny cracks near the upper and lower loading sections of the specimen. Among them, the crack distribution of the S1 and S2 specimens is the most complex, but they never deviate from the center of the disc. The fracture positions of the disc specimens are relatively concentrated, lacking a three-dimensional effect. The fracture surface distribution of the spherical specimen is more random, without a pre-estimated fracture surface, showing a more obvious three-dimensional effect. The resulting fracture surface is the weakest surface of the rock specimen, which can better characterize the true fracture of the three-dimensional rock.

[0082] Numerical simulation studies:

[0083] Comparison of stress cloud distribution of spherical specimens and Brazilian disc specimens. Firstly, ABAQUS finite element software was used to study the horizontal stress distribution of spherical specimens and Brazilian disc specimens during axial compression ( Figure 5 , Figure 6 ).

[0084] According to the stress distribution cloud map, it can be found that the stress concentration area of ​​the Brazilian disk is relatively small, mainly concentrated in the center of the disk, and distributed in an elliptical shape to both sides. The stress in the center of the disk is the largest. According to the stress distribution characteristics, it can be obtained that the possible fracture surface of the Brazilian disk specimen must be in the stress concentration area ( Figure 5 ). That is, the potential fracture surface of the Brazilian disc specimen is at the center of the specimen, which is equivalent to presetting the tensile fracture surface. Therefore, the tensile strength value obtained by using the Brazilian disc specimen is closer to the tensile strength value of this tensile fracture surface, has a strong two-dimensional feature, lacks a three-dimensional effect, and is difficult to reflect the tensile strength of a three-dimensional rock specimen.

[0085] According to the stress distribution of spherical specimens, it can be found that the stress concentration area of ​​spherical specimens is more widely distributed and is distributed in a ring shape on the three-dimensional surface. This distribution feature intuitively reflects the three-dimensional characteristics of the rock. The stress concentration degree is three-dimensional, which helps to increase the randomness of the crack rupture direction and has more potential rupture surfaces ( Figure 6 ). Therefore, the tensile strength value measured is the minimum tensile strength value of each section of the three-dimensional sample, which can better represent the tensile strength value of the three-dimensional rock sample. This is consistent with the above-mentioned indoor test results.

[0086] Cohesive force numerical model: In order to further analyze the difference in tensile strength of the two specimens and the specimen rupture process, the cohesive force numerical model was used for simulation research. The cohesive zone model was first proposed by Dugdale and Barenblatt. This model can better solve the problem of crack tip singularity and is widely used in complex crack propagation research.

[0087] Numerical calculation principle:

[0088] (1) Cohesive unit constitutive equation

[0089] The cohesive element adopts a linear elastic constitutive model based on the traction separation law. Before the damage begins, the stress-strain satisfies the linear elastic relationship, that is:

[0090]

[0091] Among them, the symbol t represents stress, ε represents strain, subscript n represents the normal direction, subscripts s and t represent the two tangential directions, and K is the unit stiffness.

[0092] (2) Crack extension criteria:

[0093] 1) Damage initiation criterion: This embodiment adopts the maximum principal stress criterion as the crack initiation criterion:

[0094]

[0095] When f reaches within the tolerance range: 1.0≤f≤1.0+ftol, damage begins. The tolerance ftol takes the system default error of 0.05. is the critical maximum principal stress value, <σ max > is represented as:

[0096]

[0097] That is, the unit will not produce initial damage under pure compression state.

[0098] 2) Damage evolution criterion: The damage evolution law is used to describe the rate of material stiffness degradation. The damage variable D is defined to represent the overall damage of the material. D evolves from 0 to 1 during the damage process. The influence of the damage variable on the stress component can be given by the following formula:

[0099]

[0100] in, are the three stress components predicted by the elastic-plastic traction separation behavior combined with the current strain. In order to describe the damage evolution under the combined action of normal deformation and shear deformation on the interface, the effective displacement is introduced and defined as:

[0101]

[0102] The damage variable D in this embodiment is expressed in a linear softening form based on effective displacement:

[0103]

[0104] in, is the effective displacement at failure; is the effective displacement at the beginning of damage evolution; is the maximum effective displacement during the loading process.

[0105] (3) Acoustic emission numerical simulation method: Acoustic emission (AE) technology is an effective means of detecting crack extension. It can continuously and in real time monitor the generation and development of cracks and has been widely used in the field of rock mechanics. In order to deeply analyze the crack extension process, this embodiment is based on the basic idea of ​​the acoustic emission method, uses Python programming language to carry out secondary development of ABAQUS software, and combines MATLAB programming to process simulation data to implement acoustic emission numerical simulation technology in finite element, and accurately obtain AE positioning map and AE characteristic parameters. The acoustic emission simulation method has been verified in the literature combined with indoor experiments. Its basic ideas are as follows:

[0106] First, extract all damaged units and the time of damage onset, and count the number of damaged units at different times as the number of acoustic emission events; secondly, obtain the node coordinates and dissipated energy of the damaged unit, so as to calculate the location coordinates of the acoustic emission event point and the acoustic emission energy; finally, obtain the damage unit parameter MMIXDME to determine the crack rupture type. The MMIXDME parameter is defined as follows:

[0107]

[0108] Among them, G n , G s , G tThe MMIXDME value represents the fracture energy of three types of fractures. When the MMIXDME value is 0, it represents pure tensile fracture, when it is 1, it represents pure shear fracture, and in between, it represents a mixed fracture of tension and shear.

[0109] Numerical model: Rocks, as mineral aggregates, are composed of various mineral particles and have mineral heterogeneity. To establish a numerical model for rock mineral heterogeneity, this example determines the types and proportions of minerals contained in rocks based on the results of XRD mineral composition analysis of sandstone (Table 3). ABAQUS simulation software is secondary developed through Python programming, using grid units to characterize mineral particles and assigning mechanical parameters to different minerals, thereby realizing the heterogeneity of rock minerals.

[0110] Table 3 Mineral composition and parameters

[0111]

[0112] At the same time, through secondary development, zero-thickness cohesive units are embedded in the middle of all solid units, and fracture parameters are set for the cohesive units to achieve complex crack network simulation ( Figure 7 ).

[0113] The simulation parameters were determined based on the test results. The tensile strengths of the spherical specimens and disk specimens were 3.3MPa and 6.24MPa, respectively. The initial damage displacements were 0.0334mm and 0.0322mm, respectively. The shear strength was set to 5 times the tensile strength. The total number of mesh elements for the spherical specimens was 42,963, including 28,416 four-node linear tetrahedral elements (C3D4) and 14,547 three-dimensional six-node bonding elements (COH3D6). The total number of disk specimen elements was 82,404, including 54,514 solid elements and 27,890 cohesive elements, respectively. The simulation used explicit dynamics calculations, set global self-contact, and the maximum loading displacement was 2mm.

[0114] 4.2.3 Numerical simulation results

[0115] Based on the above acoustic emission numerical simulation method, the number of acoustic emission events during the loading process is extracted, and the time-load curve and the corresponding acoustic emission event distribution diagram are obtained ( Figure 8 ).Depend on Figure 8 It can be seen that the load curves and acoustic emission event distributions of the spherical specimens and disc specimens are similar. The load curves have four obvious stages, corresponding to the compaction stage, elastic stage, plastic stage, and post-peak stage. The difference is that the peak point of the spherical specimen appears later. This is because the stress concentration of the spherical specimen is weaker, and it takes more time to cause the rock to fail, which is consistent with the larger rupture displacement of the spherical specimen in the indoor test.

[0116] In addition, according to the distribution of acoustic emission events, it can be found that a small number of acoustic emission events occurred before the peak load of both samples, and the maximum acoustic emission events occurred in the post-peak stage. The difference is that the acoustic emission events of the spherical sample are distributed in a wider time domain, showing obvious double cluster characteristics, while the number of acoustic emission events of the disc sample is more concentrated, showing a single cluster characteristic. This distribution feature is closely related to the stress condition of the rock sample, and this phenomenon can be more intuitively understood by analyzing the spatiotemporal evolution of acoustic emission.

[0117] Therefore, according to the characteristics of the time-load curve and the distribution law of acoustic emission events, four points (point A, point B, point C, and point D) were selected respectively, and the spatiotemporal evolution process of acoustic emission at different loading stages was obtained based on the secondary developed acoustic emission simulation technology ( Fig. 9 ). The colors are used to represent different fracture types, red for pure tensile fracture and purple for pure shear fracture, and the size of the positioning point is used to characterize the acoustic emission energy.

[0118] From the spatiotemporal evolution of acoustic emission, it can be found that both the spherical specimen and the disc specimen produce shear fracture at the end (loading point) at the initial stage of loading. As the loading progresses, tensile fracture gradually occurs and expands to the middle of the specimen. Since the stress concentration of the spherical specimen is weaker and the stress distribution is wider, more weak acoustic emission signals are generated at the initial stage of loading and dispersed near the loading point. The Brazilian disc specimen is subjected to more concentrated force and only produces micro-fractures in the area of ​​maximum stress concentration. This also explains the wide temporal domain of the distribution of acoustic emission events of the spherical specimen.

[0119] On the whole, the acoustic emission event points of the spherical specimen are relatively scattered, showing three-dimensional spatial characteristics. Among them, a large number of acoustic emission events are densely distributed in the lower part of the specimen. Combined with the final crack rupture morphology, it can be seen that bifurcated secondary cracks are generated in the lower and middle parts of the specimen, so there are more acoustic emission events. As the loading progresses, the weakest fracture surface of the spherical specimen in three-dimensional space gradually appears, and finally a high-energy main crack is generated. The acoustic emission events of the disc specimen are mainly concentrated in the middle of the disc, and the main fracture surface is also in the middle of the disc, while a larger fracture crack is generated at the end loading point. The numerical simulation results are consistent with the above-mentioned stress analysis and indoor test results. The spherical specimen can better reflect the three-dimensional effect of rock.

[0120] The number of acoustic emission events corresponding to different rock fracture types was further counted ( Fig.10 ). Since the number of grid cells of the spherical sample and the disc sample is different, the number of acoustic emission events is normalized for easy comparison. Fig.10It can be seen that both the spherical specimen and the disc specimen are mainly tensile fractures, and the number of tensile fracture acoustic emission events is much greater than the number of shear fracture events. The total number of AE events, tensile fracture AE events, and shear fracture AE events of the disc specimen are all greater than those of the spherical specimen. This is because the stress concentration of the disc specimen is greater, and more micro fractures are produced in the thickness direction of the maximum principal stress surface, while the stress of the spherical specimen is dispersed in the entire three-dimensional space, and the stress intensity is relatively small, which is not conducive to the generation of a large number of micro fractures. However, this feature is conducive to screening the weakest section, so that the spherical specimen can penetrate along the weakest fracture surface, and the three-dimensional effect is stronger. At the same time, the tension-shear ratio of the spherical specimen is much greater than that of the Brazilian disc specimen, and the spherical specimen can better reflect the tensile fracture resistance of the rock.

[0121] When using a Brazilian disc for tensile strength testing, no matter what the loading conditions are, a splitting failure dominated by tensile stress will always occur on the predetermined failure surface, thereby determining the tensile strength of the rock. Does the same rule apply to spherical specimens? This example uses finite element software to obtain the σ x and σ z Stress cloud diagram ( Fig.11 ).

[0122] It can be found from the cloud diagram that σ x and σ z Tensile stress concentration occurs in all of them, and the tensile stress dominates in the three-dimensional space in the middle of the loading point, satisfying the basic tensile fracture conditions. x , σ y and σ z Stress distribution data in three directions ( Fig.12 ).

[0123] Depend on Fig.12 The stress distribution can be found: the diameter of the spherical specimen at the loading point is σ x and σ z coincide with 80% of the tensile stress being nearly equal, σ y It shows a compressive stress state, and the minimum compressive stress value is also 4 times the maximum tensile stress value, so the spherical specimen meets the tensile rupture conditions.

[0124] In addition, existing studies have shown that the tensile strength value of rock will decrease as the size of the Brazilian disc specimen increases. It is generally believed that the size effect is caused by microcracks or microdefects inside the rock. Large-sized specimens may contain more microcracks inside, which leads to a decrease in the tensile strength of the rock. The tensile strength value obtained by the spherical specimen in this embodiment is smaller than that of the Brazilian splitting method. The reason is inferred to be: the volume of the spherical specimen with the same diameter is larger than that of the disc specimen. In three-dimensional space, the spherical specimen may contain more microdefects inside, and the potential rupture area of ​​the spherical specimen is larger under the action of the three-dimensional tensile stress field, resulting in a smaller tensile strength value. The tensile strength value obtained by the spherical specimen may correspond to a large-sized Brazilian disc test result. Of course, this requires further research on the size effect of the spherical specimen, and also requires comparison of the tensile strength difference between spherical specimens and disc specimens of the same volume.

[0125] This embodiment uses a spherical specimen to perform a tensile strength test, and combines numerical simulation methods to perform a comparative analysis with a traditional Brazilian disc specimen, and the following conclusions can be drawn:

[0126] (1) There is a significant difference in the stress distribution between the spherical specimen and the Brazilian disc specimen. The stress cloud distribution can indirectly characterize the possible location of the crack. The potential fracture surface of the Brazilian disc specimen is relatively single, while the spherical specimen has multiple potential fracture surfaces and has random fracture.

[0127] (2) The displacement-load curves of the spherical specimen and the Brazilian disc specimen show the same trend of change. Both specimens show obvious brittle characteristics, and the plastic stage is not obvious. The acoustic emission events appear sporadically before the peak and increase sharply after the peak.

[0128] (3) Since the fracture surface of the spherical specimen is more random, the crack will break along the weakest section, so the tensile strength value obtained is smaller, and the average tensile strength value is only 3.3MPa. The three-dimensional characteristics of the Brazilian disc specimen are weaker, and the tensile strength value obtained is equivalent to the strength value of a certain section. The average tensile strength is 6.24MPa, which is about twice that of the spherical specimen. The tensile strength value obtained by the spherical specimen has a smaller standard deviation and a higher tension-shear ratio, which can better reflect the true tensile properties of three-dimensional rocks.

[0129] (4) The cracks of the Brazilian disc specimen are more concentrated, mainly distributed in the center of the disc, and cannot reflect the three-dimensional effect of the rock sample. The spherical specimen does not limit the fracture surface of the rock, and the fracture surface distribution is more random. The acoustic emission events are discretely distributed in the three-dimensional space, showing a more obvious three-dimensional characteristic, which is conducive to the generation of the weakest fracture surface. Compared with the Brazilian disc specimen, the use of spherical specimens for tensile strength testing has its unique advantages.

[0130] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for testing the tensile strength of a rock sample, characterized in that: include: Step 1: obtaining rock samples, wherein the rock samples include spherical samples and disc samples; Step 2: Perform mechanical tests on each of the rock samples, record experimental data and calculate the tensile strength value of each of the rock samples, and determine the three-dimensional tensile strength of each of the rock samples based on the tensile strength value of each of the rock samples; Step 3: Based on the experimental data and the tensile strength value, a numerical model of each of the rock samples is established in combination with numerical software, and the established numerical model is axially compressed to obtain stress distribution data and potential fracture surfaces of each of the rock samples, and the three-dimensional tensile strength of each of the rock samples is determined based on the stress distribution data and potential fracture surfaces corresponding to each of the rock samples; Step 4: simulating the fracture process of each of the rock samples according to the cohesive force numerical model, and obtaining the acoustic emission events during the fracture process using the acoustic emission technology; judging the three-dimensional tensile strength of each of the rock samples based on the acoustic emission events corresponding to each of the rock samples; Step 5: Based on the judgment results of steps 2 to 4, the three-dimensional tensile strength of each rock sample is compared to obtain a comparison result, wherein the comparison result is that the three-dimensional tensile strength of the spherical sample is less than the three-dimensional tensile strength of the disc sample.

2. A rock sample tensile strength testing method according to claim 1, characterized in that: Before carrying out mechanical tests on the rock samples, the method further comprises: Vaseline is applied to both ends of each rock sample to obtain each pretreated rock sample, and mechanical tests are performed based on each pretreated rock sample.

3. A rock sample tensile strength testing method according to claim 1, characterized in that: The mechanical test on each of the rock samples specifically includes: Mechanical tests are performed on each of the rock samples using a rock mechanics testing machine combined with a preset loading rate.

4. A rock sample tensile strength testing method according to claim 1, characterized in that: The recording of experimental data and calculation of the tensile strength value of each rock sample specifically includes: During the mechanical test of each of the rock samples, a displacement-load curve is recorded; The peak load is extracted from the displacement-load curve and the tensile strength value is calculated.

5. A rock sample tensile strength testing method according to claim 1, characterized in that: The determining of the three-dimensional tensile strength of each rock sample based on the tensile strength value of each rock sample specifically includes: The standard deviation corresponding to the tensile strength value of each of the rock samples is calculated. When the standard deviation is less than a preset first threshold value, the rock sample has low three-dimensional tensile strength.

6. A rock sample tensile strength testing method according to claim 1, characterized in that: The process of obtaining the stress distribution data and potential fracture surface of each rock sample specifically includes: Establishing a geometric model of the rock sample in ABAQUS based on the experimental data and the tensile strength value; The boundary conditions and loading methods during the axial compression process are simulated in the constructed geometric model, and finite element analysis is performed to obtain the horizontal stress distribution data of the rock sample during the axial compression process, and the potential fracture surface of the rock sample is determined based on the horizontal stress distribution data.

7. A rock sample tensile strength testing method according to claim 1, characterized in that: The determining of the three-dimensional tensile strength of each rock sample based on the stress distribution data and potential fracture surface corresponding to each rock sample specifically includes: When the stress distribution data corresponding to the rock sample is distributed in a ring shape on a three-dimensional surface, the corresponding rock sample has a low three-dimensional tensile strength; When the potential fracture surfaces corresponding to the rock sample are randomly distributed, the corresponding rock sample has low three-dimensional tensile strength; when the potential fracture surfaces corresponding to the rock sample are predictedly distributed, the corresponding rock sample has high three-dimensional tensile strength.

8. A rock sample tensile strength testing method according to claim 1, characterized in that: The fracture process of the spherical rock sample is simulated according to the cohesive force numerical model, specifically including: A linear elastic constitutive model is used to describe the stress-strain relationship of the cohesive unit before damage, and the crack extension criterion is set. A numerical model of mineral heterogeneity is established based on the results of mineral composition analysis. A zero-thickness cohesive unit is embedded in the middle of the solid unit, and fracture parameters are set to complete the cohesive force numerical model of the rock sample. Based on the acoustic emission numerical simulation method, the time-load curve and acoustic emission event distribution diagram in the cohesive force numerical model are obtained.

9. A rock sample tensile strength testing method according to claim 1, characterized in that: The determining of the three-dimensional tensile strength of each rock sample based on the acoustic emission events corresponding to each rock sample specifically includes: When the acoustic emission events corresponding to the rock sample are discretely distributed in three-dimensional space, the corresponding rock sample has low three-dimensional tensile strength.